Uniqueness for Optimal control problems of two-dimensional second grade fluids - Almeida, Adilson (2022)
Nikolai V. Chemetov was supported by the project no. 2021/03758-8 of Regular Research Grant-FAPESP, Brazil, and by the Program of "Docentes Novos", Process no. 20.1.4175.1.0 of Universidade de Sao Paulo. F. Cipriano was partially supported by the Fundacao para a Ciencia e a Tec-nologia.